2021
DOI: 10.1186/s12909-021-02730-8
|View full text |Cite
|
Sign up to set email alerts
|

An online discussion between students and teachers: a way forward for meaningful teacher feedback?

Abstract: Background Student evaluation is an essential component in feedback processes in faculty and learner development. Ease of use and low cost have made paper evaluation forms a popular method within teaching programmes, but they are often seen as a formality, offering variable value towards the improvement of teaching. Students report poor motivation to engage with existing feedback tools whilst teachers describe receiving vague, contradicting, or irrelevant information. We believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…An appreciable number of the participants (42.4 %) regarded their instructor’s feedback on their work and progress as poor. Feedback is an important component of effective learnerning [ 46 ]. Feedback provision supports the opportunity for enhanced academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…An appreciable number of the participants (42.4 %) regarded their instructor’s feedback on their work and progress as poor. Feedback is an important component of effective learnerning [ 46 ]. Feedback provision supports the opportunity for enhanced academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Successful online teaching depends on the use of authentic learning experiences, assessment tools, and feedback systems to increase the involvement and motivation of pre-service teachers (Byrka et al, 2022). Research conducted by Hunukumbure et al (2021) has demonstrated that offering feedback on teaching tactics substantially enhances students' motivation and engagement in the learning process. Additionally, faculty calibration and the utilization of instructional rubrics are acknowledged as efficacious approaches to strengthen the caliber of feedback and assessment in educational environments (Gosselin and Golick, 2020).…”
Section: Research Questionmentioning
confidence: 99%
“…In the health professions, feedback from learners has been reported as a powerful motivator of clinicians' commitment to teaching [1,2]. That said, teachers also report receiving brief, vague and generic feedback from learners, oftentimes months after a given teaching encounter, which can leave them feeling frustrated and uncertain regarding interpretation and application [3][4][5][6]. While research has highlighted challenges learners face in providing feedback to their teachers, we lack a fulsome understanding of how these challenges impact learners' approaches towards upward feedback, why these challenges lead learners to resort to vague or generic feedback, and which teachers might be most susceptible to receiving suboptimal feedback.…”
Section: Introductionmentioning
confidence: 99%
“…That said, research within medical education and the broader field of education have highlighted common challenges learners face when assessing or giving feedback to their teachers: 1) having to complete too many forms that are time consuming [5]; 2) feeling ill-equipped to provide feedback to teachers [3,6,11]; 3) feeling uncertain about teachers' receptivity and the impact of their feedback on teaching practices [6,[11][12][13]; and, 4) experiencing power imbalances and fearing consequence [3,11,12]. These issues have contributed to a situation in which concerns regarding the validity and utility of SETs are widespread [14][15][16], making it likely that the value of narratives from learners [17] is all too easily overlooked.…”
Section: Introductionmentioning
confidence: 99%